The Covid-19 disease and policy response to mitigate the economic impact in the EU - Zinecker, Marek; Doubravský, Karel; Balcerzak, Adam P.; Pietrzak, Michał Bernard; Dohnal, Mirko (Technological and Economic Development of Economy, 2021)
This study aims to understand how Covid-19 contagious disease and the EU’s policy response may affect macroeconomic performance. Previous studies on this topic have used historical data sets on “rare macroeconomic disasters” such as Great Influenza to assess the impact of the current pandemic on the global economy. The authors examine the main channels of transmission and targeted policy response to mitigate crisis qualitatively. The authors use heuristics and apply qualitative trend-based analysis because the current pandemic is a unique event for which accurate quantitative data are not currently available. Researchers first identify a set of eight variables based on previous academic theories. They then express each variable as a trend: ascending, descending, and constant. The numerical calculations consist of 17 scenarios, supplemented by 24 transitions and a transition graph. Besides, the article proposes a graphical solution to examine the change in GDP that is too small. The results of the study should be understood as a reference point to allow both private and public stakeholders to understand better the relationship between the observed variables and their dynamics. The research provides a comprehensive list of future events to examine further the implications for the economy as a whole and each individual. First published online 26 April 2021